Poesía '68 : para una historia imposible : escritura y sociedad, 1968-1978 - Méndez Rubio, Antonio, 1967- (Documentos para la historia de la poesía española del siglo XX ;, 2004)
Twenty noted poets respond to a questionnaire concerning their poetry and the social and cultural environment in which they work.